Management of Acute Liver Failure: Update 2022 - Tujios, Shannan; Stravitz, R. Todd; Lee, William M. (Seminars in Liver Disease, 2022)
Abbreviated pathogenesis and clinical course of the acute liver failure syndrome. The pathogenesis and clinical course of the syndrome of acute liver failure (ALF) differs depending upon the etiology of the primary liver injury. In turn, the severity of the liver injury and resulting synthetic failure is often the primary determinant of whether a patient is referred for emergency liver transplantation. Injuries by viral etiologies trigger the innate immune system via pathogen-associated molecular patterns (PAMPs), while toxin-induced (and presumably ischemia-induced) injuries do so via damage-associated molecular patterns (DAMPs). The course of the clinical syndrome further depends upon the relative intensity and composition of cytokine release, resulting in an early proinflammatory phenotype (SIRS) and later compensatory anti-inflammatory response phenotype (CARS). The outcomes of overwhelming immune activation are the systemic (extrahepatic) features of ALF (cardiovascular collapse, cerebral edema, acute kidney injury, respiratory failure, sepsis) which ultimately determine the likelihood of death.Acute liver failure (ALF) continues to carry a high risk of mortality or the need for transplantation despite recent improvements in overall outcomes over the past two decades. Optimal management begins with identifying that liver failure is indeed present and its etiology, since outcomes and the need for transplantation vary widely across the different etiologies. Most causes of ALF can be divided into hyperacute (ischemia and acetaminophen) and subacute types (other etiologies), based on time of evolution of signs and symptoms of liver failure; the former evolve in 3 to 4 days and the latter typically in 2 to 4 weeks. Both involve intense release of cytokines and hepatocellular contents into the circulation with multiorgan effects/consequences.Management involves optimizing fluid balance and cardiovascular support, including the use of continuous renal replacement therapy, vasopressors, and pulmonary ventilation. Early evaluation for liver transplantation is advised particularly for acetaminophen toxicity, which evolves so rapidly that delay is likely to lead to death.Vasopressor support, high-grade hepatic encephalopathy, and unfavorable (subacute) etiologies heighten the need for urgent listing for liver transplantation. Prognostic scores such as Kings Criteria, Model for End-Stage Liver Disease, and the Acute Liver Failure Group prognostic index take these features into account and provide reasonable but imperfect predictive accuracy. Future treatments may include liver support devices and/or agents that improve hepatocyte regeneration.
Keywords: encephalopathy; coagulopathy; hepatocyte injury; renal replacement therapy; prognostic score